ANALISIS PENGARUH DIGITAL MARKETING, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA FORE COFFEE - Dwi Ambarwati, (2020)
This study aims to determine the effect of Digital Marketing, product quality and price on purchasing decisions at Fore Coffee. The dependent variable in this study is the purchase decision. The independent variables are Digital Marketing, product quality and price. In this study the sampling technique used is non probability sampling. The sampling method uses a purposive sampling technique of 75 respondents. The type of data used in this study is primary data. Data obtained in this study by distributing questionnaires through Google form provided directly to respondents. The analysis method is processed using Partial Least Square (PLS). the results of this study indicate that the Digital Marketing variable has a positive and significant effect on purchasing decisions, while the product quality and price variables have no significant effect on purchasing decisions.